2014
DOI: 10.1002/lsm.22260
|View full text |Cite
|
Sign up to set email alerts
|

Fractional laser for vitiligo treated by 10 600 nm ablative fractional carbon dioxide laser followed by sun exposure

Abstract: All patients treated with both, laser sessions and sun exposure, improved their chronic NSV lesions. Improvement was less significant in patients who exhibited vitiligo lesions over articular surfaces such as elbows and underarms. The best results were observed in vitiligo plaques located on the face, neck and legs. Consequently, fractional CO2 laser followed by sun exposure could be considered as an alternative modality for the treatment of refractory vitiligo, especially in sunny regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…According to the study by Shin et al., two sessions of half‐body fractional CO 2 laser therapy at a 2‐month interval combined with twice weekly whole‐body NB‐UVB phototherapy result in significantly higher improvement rate compared to the contralateral side which did not receive fractional CO 2 laser treatment. Helou et al . found that monthly sessions for 3 months of fractional CO 2 laser treatment followed by 2‐hour sunlight exposure on daily basis result in improvement in vitiligo, which was assessed by the physician and by patient's satisfaction.…”
Section: Discussionmentioning
confidence: 57%
“…According to the study by Shin et al., two sessions of half‐body fractional CO 2 laser therapy at a 2‐month interval combined with twice weekly whole‐body NB‐UVB phototherapy result in significantly higher improvement rate compared to the contralateral side which did not receive fractional CO 2 laser treatment. Helou et al . found that monthly sessions for 3 months of fractional CO 2 laser treatment followed by 2‐hour sunlight exposure on daily basis result in improvement in vitiligo, which was assessed by the physician and by patient's satisfaction.…”
Section: Discussionmentioning
confidence: 57%
“…In 2004, fractional laser therapy was developed to reduce the side effects of total ablative lasers. Recently, the fractional CO 2 laser followed by topical steroids combined with NB-UVB or sun exposure has been proved to be effective in the treatment of refractory vitiligo [12,13]. In 2015, we also reported a triple combination treatment with fractional CO 2 laser assisting delivery of topical betamethasone solution plus NB-UVB phototherapy for refractory vitiligo and achieved some encouraging results [14].…”
Section: Discussionmentioning
confidence: 97%
“…Three months posttreatment (M3) and 6 months post-treatment (M6), the response to the treatment was assessed by two blinded dermatologists. Depending on the extent of re-pigmentation, the response to the treatment was graded as: no or minimal (<25%), moderate (25-49%), marked (50-74%), excellent (≥75%) [12,13]. Any side effect was recorded during the procedure.…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations